THE INFLUENCE OF A POLYPEPTIDE PREPARATION ON A STRUCTURAL-FUNCTIONAL STATE PERIODONT IN ADJURANT PERIODONITIS (EXPERIMENTAL RESEARCH) - G.M. Silenko; O.B. Belikov; N.I. Belikova; M.V. Khrebor; Y.I. Silenko (Український стоматологічний альманах)
The aim of this article is to study the indices of cellular, humoral immunity and nonspecific resistance, indices of free radical lipid oxidation and thrombocytoactive properties of periodontal tissues in animals with adjuvant periodontitis.